The Effect of Financial Ratio Performance on Credit Distribution (Study on Commercial Banks in Indonesia for the 2020-2022 Period) - Charakas, Nana Yohana; Putri, Ika Swasti (Economics and Business Solutions Journal, 2023)
The goal to be realized in this study is to provide partial or simultaneous empirical evidence of the effect of CAR, NPL, LDR, ROA, DPK on lending.  In this research using secondary data. The sample in this research amounted to 60 data using a purposive sampling technique. In analyzing the data using multiple linear regression analysis test, t test, F test and the coefficient of determination.  Relying on the results obtained in partial and simultaneous research CAR, NPL, ROA have a non-significant positive effect on lending, LDR, DPK have a significant positive influence on lending. The results of the calculation of the coefficient of determination are 99.2% while the remaining 0.8%.Keywords : Lending, CAR, NPL, LDR, ROA, DPK.